A convenient luminescence assay of ferroportin internalization to study its interaction with hepcidin. (11th March 2013) - Song, Ge; Jiang, Qian; Xu, Ting; Liu, Ya‐Li; Xu, Zeng‐Guang; Guo, Zhan‐Yun
<x xml:space="preserve">Abstract</x> Hepcidin is a liver‐secreted small disulfide‐rich peptide that plays a key role in iron homeostasis by binding and mediating the internalization and degradation of the only iron efflux transporter so far known, ferroportin (Fpn). To study hepcidin–Fpn interactions, in the present study we established a convenient luminescence assay for the quantitative measurement of hepcidin‐induced Fpn internalization by fusing a small nanoluciferase (NanoLuc, 171 amino acids) at the Fpn C‐terminus. Once the NanoLuc‐tagged Fpn was internalized, the measured luminescence was significantly decreased when assayed with the intact transiently transfected cells and an inducible expression system. Through the coexpression of a NanoLuc‐tagged Fpn and an enhanced green fluorescent protein (EGFP)‐tagged Fpn by the use of an inducible bidirectional promoter, we could measure the hepcidin‐induced Fpn internalization qualitatively and quantitatively on the basis of the fluorescence of the tagged EGFP and the luminescence of the tagged NanoLuc. Thus, our present study provides a novel and convenient assay for measuring the hepcidin–Fpn interaction qualitatively and quantitatively. Through coexpression of a NanoLuc‐tagged wild‐type Fpn and an EGFP‐tagged hepcidin‐insensitive mutant [C326S]Fpn, we demonstrated that the mutant Fpn had no effect on hepcidin‐induced internalization of wild‐type Fpn, suggesting that wild‐type Fpn and mutant Fpn are functionally independent.